Gamifying Grammar and Vocabulary Formative Assessment Using WordWall Application: Its Design, Students’ Engagement, and Motivation - Adimawati Helingo; Alvons Habibie (Journal of Innovative and Creativity, 2025)
The evaluation model for game-based learning has garnered significant attention from researchers today. Game-based assessment models are believed to offer a fresh perspective compared to the conventional assessment models dominating the field. This research aims to develop a Vocabulary and Grammar question model based on games, integrated into applications such as Wallword and Educandy. After designing these questions, another objective is to explore the extent to which the use of Wallword and Educandy influences the enhancement of students' engagement and learning motivation. This study utilizes a Research and Development (R&D) design, specifically employing the Four D approach. The Four D type of R&D consists of four stages, namely Define, Design, Develop, and Disseminate. The respondents involved in this research comprise 25 English language students from IAIN Sultan Amai Gorontalo and 15 English Literature students from Universitas Muhammadiyah. The results showed that The research design encompasses three main components: creating a structured test framework, selecting appropriate templates for Wallword and Educandy, and developing the test items with specified difficulty levels. After implementing the game-based Vocabulary and Grammar assessment model, observations revealed high student engagement and motivation, particularly due to their enthusiasm for technology-enhanced learning through Wallword and Educandy platforms.